Dotawo: A Journal of Nubian Studies 7 Comparative Northern East Sudanic Linguistics - Gerven Oei, van (Punctum Books, 2020)
Dotawo: A Journal of Nubian Studies offers a platform in which the old meets the new, in which archaeological, papyrological, and philological research into Meroitic, Old Nubian, Coptic, Greek, and Arabic sources confront current investigations in modern anthropology and ethnography, Nilo-Saharan linguistics, and the critical and theoretical approaches of postcolonial and African studies. Dotawo gives a common home to the past, present, and future of one of the richest areas of research in African studies. It offers a crossroads where papyrus can meet the internet, scribes meet critical thinkers, and the promises of growing nations meet the accomplishments of older kingdoms. The seventh issue of Dotawo is dedicated to Comparative Northern East Sudanic linguistics, offering new insights in the historical connections between the Nubian languages and other members of the NES family such as Nyima, Nara, and Meroitic. A special focus is placed on comparative morphology.